Comparative study between two innovative clusters in Morocco and Italy - Najiba El Amrani El Idrissi; Ilham Zerrouk; Naoual Zerrari; Salvatore Monni (Insights into Regional Development)
The paper takes place in the research field of the European project “Cluster Development Med” (Horizon 2020) focusing on the innovation and technology in the sustainable development area. Authors suggest a comparative study, which allows selecting the most innovative clusters in Morocco and Italy, and making comparisons between and within them. The analysis defines the weaknesses and strengths in the both examined clusters and embrace three dimensions of cluster activity, so called, “Humain and Material Resources, Activities, Processes and strategies”. In this paper, we start by giving a global presentation of Moroccan clusters, their history and geolocation. As a first case of study, we focused on the “Maroc Numeric Cluster” (MNC) manely on its limitations and weaknesses. Thus, in the second case study, we present a cluster that is the beating heart of Italian excellence in the energy sector (Lombardy Energy Cleantech Cluster LE2C). The aim of this paper is to present the LE2C strengths and successful strategies in order to adapt them to the MNC cluster so that it can promote and accelerate again with a successfull proccess.